Role of government in public health: Current scenario in India and future scope - Subitha Lakshminarayanan (Wolters Kluwer Medknow Publications, 2011)
The new agenda for Public Health in India includes the epidemiological transition, demographical transition, environmental changes and social determinants of health. Based on the principles outlined at Alma-Ata in 1978, there is an urgent call for revitalizing primary health care in order to meet these challenges. The role of the government in influencing population health is not limited within the health sector but also by various sectors outside the health systems. This article is a literature review of the existing government machinery for public health needs in India, its success, limitations and future scope. Health system strengthening, human resource development and capacity building and regulation in public health are important areas within the health sector. Contribution to health of a population also derives from social determinants of health like living conditions, nutrition, safe drinking water, sanitation, education, early child development and social security measures. Population stabilization, gender mainstreaming and empowerment, reducing the impact of climate change and disasters on health, improving community participation and governance issues are other important areas for action. Making public health a shared value across the various sectors is a politically challenging strategy, but such collective action is crucial.